The Perception of Russia by Young People in Post-Soviet Countries: the Experience of Sociological Assessment - M. V., Vilisov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2021)
The decades that have passed since the collapse of the USSR have identified serious challenges for Russia, the answer to which depends on the prospect of maintaining its leadership position in the integration processes in the modern post-Soviet space, not only due to objective advantages in the possession of resources, but also due to its attractiveness for the younger generation of the post-Soviet countries. The article makes an attempt of a sociological assessment of the perception of modern Russian humanitarian projects by young people in post-Soviet countries, their willingness to join the international educational projects proposed by Russia and build a trajectory of professional development, taking into account the opportunities available in Russia. The authors draw attention to the need for regular monitoring of the perception of Russia by the youth of the post-Soviet countries in order to adapt the proposed programs of international cooperation to the needs of the target audience, and also offer a methodology for its construction.